Pengembangan e-Modul Bryophyta Dengan Kajian Islam Sebagai Alternatif Bahan Ajar Di Era New Normal - Linda Amalia Saragih; Indayana Tanjung; Efrida Pima Sari Tambunan (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2021)
This study aims to develop additional teaching materials in the form of e-Modul Bryophyta dengan Kajian Islam, as well as to determine the quality of the products developed based on the assessment of several validations, teachers, and students as respondents. The data collection instrument used a questionnaire. Descriptive qualitative and quantitative data analysis. The results of the research obtained indicate that the Bryophyta e-Module with Islamic Studies developed as a whole has the quality Very Fit for use in teaching and learning activities. With the percentage results from material experts of 89.2% with Very Feasible criteria, from media experts of 71.6% with Eligible criteria, from Islamic Religion experts of 82.6% with Very Appropriate criteria and an assessment of the teacher of 82.5% with criteria Very Eligible for use in teaching and learning activities. Meanwhile, the response of students obtained the overall percentage of small and large group tests of 85.2% with very attractive criteria. Thus, it can be concluded that e-Modul Bryophyta dengan Kajian Islam, which was developed with the Borg Gall model, is feasible and very attractive to be used as teaching material for students in class X MIA in Ma, especially in Bryophyta lessons. Penelitian ini bertujuan untuk mengembangkan bahan ajar tambahan berupa e-Modul Bryophyta dengan Kajian Islam serta mengetahui kualitas produk yang dikembangkan berdasarkan penilaian dari beberapa validasi, guru dan peserta didik sebagai responden. Instrumen pengambilan data menggunakan angket. Analisis data secara deskriptif kualitatif dan kuantitatif. Hasil penelitian yang diperoleh menunjukkan bahwa e-Modul Bryophyta dengan Kajian Islam yang dikembangkan secara keseluruhan memiliki kualitas Sangat Layak untuk digunakan didalam kegiatan belajar mengajar. Dengan hasil persentase dari ahli materi sebesar 89,2 % dengan kriteria Sangat Layak, dari ahli media sebesar 71,6 % dengan kriteria Layak, dari ahli Agama Islam sebesar 82,6% dengan kriteria Sangat Layak dan penilaian dari guru sebesar 82,5% dengan kriteria Sangat Layak untuk digunakan didalam kegiatan belajar mengajar. Sementara itu, respon peserta didik diperoleh persentase keseluruhan uji kelompok kecil dan kelompok besar sebesar 85,2 % dengan kriteria Sangat Menarik. Dengan demikian, dapat disimpulkan bahwa e-Modul Bryophyta dengan Kajian Islam yang dikembangkan dengan model Borg Gall, Layak dan Sangat Menarik untuk digunakan sebagai bahan ajar bagi siswa di kelas X MA, khususnya pada materi Bryophyta. Kata kunci: biologi, e-Modul Bryophyta, pengembangan bahan ajar DOI: http://dx.doi.org/10.23960/jbt.v9i2.22803